2019
DOI: 10.1021/acssuschemeng.9b02797
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nonsteroidal Anti-Inflammatory Drug-Based Ionic Liquids with Improved Water Solubility and Drug Delivery

Abstract: We here report the synthesis of ionic liquids (ILs) composed of the cholinium cation and anions derived from nonsteroidal anti-inflammatory drugs (NSAIDs), namely ibuprofen, ketoprofen, and (S)-naproxen, and their incorporation into bacterial nanocellulose envisaging their use in topical drug delivery systems. The chemical structure of the synthesized ILs was confirmed by spectroscopic techniques, and thermal analysis confirming their categorization as ionic liquids with melting temperatures below 100 °C and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…According to the data provided in Figure 7a, the HaCaT cells' metabolic activity after 24 h of exposure to BNC membrane (93±5% cell viability) is similar to that of the negative control (100% cell viability). Hence, the BNC membrane is non-cytotoxic to HaCaT cells, which is consistent with the results obtained in literature for this cell line [28,31], but also for other cell lines, e.g., RAW 264.7 cells [55] and adipose-derived stem cells (ADSCs) [56]. Figure 7a, the HaCaT cells' metabolic activity after 24 h of exposure to BNC membrane (93±5% cell viability) is similar to that of the negative control (100% cell viability).…”
Section: In Vitro Cytotoxicitysupporting
confidence: 92%
“…According to the data provided in Figure 7a, the HaCaT cells' metabolic activity after 24 h of exposure to BNC membrane (93±5% cell viability) is similar to that of the negative control (100% cell viability). Hence, the BNC membrane is non-cytotoxic to HaCaT cells, which is consistent with the results obtained in literature for this cell line [28,31], but also for other cell lines, e.g., RAW 264.7 cells [55] and adipose-derived stem cells (ADSCs) [56]. Figure 7a, the HaCaT cells' metabolic activity after 24 h of exposure to BNC membrane (93±5% cell viability) is similar to that of the negative control (100% cell viability).…”
Section: In Vitro Cytotoxicitysupporting
confidence: 92%
“…In this case, once the drugs are released from the lumen, the interactions with the other matrix components are important and determine the release kinetics. For instance, strong interactions have been reported to exist between IBU and the nanocellulose, 76 which could explain the slower IBU release kinetics from the HNT-SEP-CNF hybrid nanopaper as compared to SA. In addition, the openings of the nanotubes could be partially obstructed by the particular texture of the film and thus, sustained the drug release.…”
Section: Uptake Of Salicylic Acid and Ibuprofen By Hnt-sep-cnf Hybridmentioning
confidence: 99%
“…Several studies have confirmed that pure BNC membranes can be successfully loaded with multiple active pharmaceutical ingredients (APIs) (or other bioactive molecules) with different structures, solubility and hydrophilicity. For instance, neat BNC membranes have already been combined with drugs and other bioactive compounds, such as lidocaine [22,23], ibuprofen [23], caffeine [24], diclofenac [25] and amoxicillin [26] in their most common forms or formulated as ionic liquids [27,28] for cutaneous drug delivery. There are also examples of BNC-based nanocomposites being used for the cutaneous delivery of diclofenac [29] and BNC-based hybrid films for the cutaneous delivery of levofloxacin [30].…”
Section: Introductionmentioning
confidence: 99%